Silencing dissent in the wake of catastrophe? An examination of the repression dynamics following weather-related rapid-onset events in autocracies - Viktoria Jansesberger; Gabriele Spilker (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Climate change will increase the frequency of destructive weather events, such as storms and floods, posing heavy burdens on affected societies, particularly in the Global South. These disasters can create fractures between the state and its citizens, potentially leading to social unrest. To manage such situations, autocratic governments might resort to repression. This paper examines whether rapid-onset weather events influence governmental repression in autocracies in the Global South. We argue that such events could trigger repression through two pathways: government-initiated repression to prevent anti-government mobilization and reactive repression in response to existing unrest. Using spatially disaggregated event data for Africa and Latin America, and logistic regression models with fixed effects on a coarsened exact matching sample, we find that government-initiated repression becomes more likely after destructive storms and floods, while reactive repression does not. Thus, autocratic governments prefer preemptive measures over reactive ones when disasters strike.
urn:nbn:de:bsz:352-2-47tni498yq962
Keywords: 320